Unusual pulmonary metastatic pattern in a case of pancreatic cancer. (5th August 2011) - Shah, Nirav; Jubber, Akeel; Osman, Marcin; Syed, Imran
Abstract : The authors report the case of a cystic pancreatic cancer with pulmonary metastasis to illustrate the unusual radiographic halo-sign appearance of nodular/consolidative change with surrounding ground glass pattern and also to highlight the histopathological background underlying this pattern.